Yunusco (BD) Ltd.: A sister concern of Yunusco Group - Sunny, Md. Azaz Ahmed (BRAC University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2020.